Development and control of vortices over a very low aspect-ratio wing - Dong, Lei (2022)
The vortical structures over a thin rectangular wing with a very low aspect ratio (AR) of 0.277 are investigated in a wind tunnel at an effective Reynolds number of 3 × 106 . The maximum lift of this thin wing is found at an angle of attack of 42◦ . The flow separates at the leading-edge and reattaches to the wing surface, forming a strong leading-edge vortex (LEV) which plays an important role on the total lift. The results show that the induced velocity of the tip vortex (TV) increases with the angle of attack, which helps reattach the separated flow and maintains the LEV. Turbulent mixing indicated by the high Reynolds stress can be observed near the leading-edge due to an intense interaction between the LEV and the TV. The reattachment point of the LEV moves upstream closer to the wing tip, however.